Impression management through minimal narrative disclosures in integrated reports: an analysis of the top 100 JSE listed firms - Chothia, Aadil (My University, 2021)
Orientation: Two crucial aspects to corporate reporting is transparency and accountability within the Integrated Report (Leung, Parker, & Courtis, 2015). Transparency within the Integrated Report allows for the users of the report to understand the financial position and underlying economics of the firm. Narrative disclosures in the Integrated Report forms a part of the annual corporate financial report and serves as a means of communication between management and investors. Narrative disclosers can also serve as a medium for impression management strategies utilised to distract investors’ attention from a firm’s weaknesses. This can be achieved through “selectivity” which involves including or omitting certain items of information within the Integrated Report (Merkl-Davies & Brennan, 2007).Research purpose: The purpose of this study is to determine if the top 100 JSE listed companies utilise impression management strategies, specifically through minimal narrative disclosures in their Integrated Reports. This will allow the researcher to “explore the phenomenon of concealment strategy through minimal narrative disclosures. In this study, the researcher focuses on selectivity in neglecting narrative information in the Integrated Report and extends the body of knowledge relating to impression management using concealment strategy, specifically discretionary narrative disclosures. Overview of research method: This was an adaptation of a study conducted by Leung et al. (2015) and was of a quantitative nature which involved the systematic investigation of the research questions through statistical methods on the data gathered. The research involved two phases. Phase 1 involved the identification of minimal narrative disclosure firms using a disclosure corpus. Phase 2 allowed the researcher to explore the sub-research questions which involved the use of a multivariate regression model. Main Findings: The study illustrated that from the sample firms selected, 49% were classified as minimal narrative disclosure firms based on their disclosure score obtained from the disclosure checklist. The study also showed that there is no association between a firm’s current performance and their minimal narrative disclosure firm score and revealed that there is an association between a firm’s financial distress levels and the minimal narrative disclosure firm score obtained by the firm. No evidence was obtained to support that minimal narrative disclosures in Integrated Reports are associated with future performance of a minimal narrative disclosure firm (whether future performance improves or deteriorates) within the context of this research
A research report submitted to the School of Accountancy, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Commerce, 2021
Keywords: UCTD; Narrative disclosure; Minimal disclosure; Minimal narrative disclosure; Impression management; Concealment; Selectivity; Integrated Report; SDG-17: Partnerships for the goals